A Brief Overview on the Road Safety Approach in Singapore - World Bank (World Bank, Washington, DC, 2019)
The report introduces how the Safe System Approach works, with a focus on road infrastructure and road safety engineering best practices from one of the best performing countries in Southeast Asia and the Pacific, Singapore. Singapore roads are not only considered the safest in the region, they rank among the safest globally. Road safety management rules and regulations implemented in the country have resulted in significant strides in managing the effects of collision factors related to roadway design, human behavior, and vehicle attributes. As a result, road safety statistics have shown that fatalities on the Singapore road network have been steadily declining over the past decade. This is leading to a desire on the part of neighboring countries to follow Singapore's example and learn from its experience. In order to mitigate collisions attributed to vehicle inadequacies or defects, one of the measures taken in Singapore was to enforce a strict vehicle import policy. Vehicle imports are permissible from countries that have adopted and comply with recognized high vehicle safety standards. Vehicle safety compliance is particularly focused on 52 items specified by the Land Transport Authority (LTA). In addition to strict vehicle import standards, Singapore enforces a strict vehicle quota system, which regulates the number of vehicles on the road network. Additionally, vehicles are required to undergo frequent inspections. Cars between 3 and 10 years old are required to have a biennial inspection, and cars older than 10 years are required to undergo annual inspections. Furthermore, taxis are required to undergo inspections every six months. Road safety education and driver education are core tenants of Singapore's roads safety strategy. Road safety education is predominately undertaken by the Singapore Traffic Police, but nongovernmental organizations such as the National Security Coordination Secretariat contribute significantly to road safety education in Singapore.